Hyperglycaemia following immune checkpoint inhibitor therapy—Incidence, aetiology and assessment. Issue 4 (6th February 2023) - Mulla, Kaenat; Farag, Sheima; Moore, Benedict; Matharu, Sheila; Young, Kate; Larkin, James; Popat, Sanjay; Morganstein, Daniel Laurence
Abstract: Aims: We systematically studied the presence of hyperglycaemia during treatment with Immune Checkpoint Inhibitors (ICPI) for cancer, in those with and without diabetes at baseline, and determined the cause of new‐onset hyperglycaemia, Methods: Retrospective review of electronic records of those receiving an ICPI for melanoma, lung or renal cancer. Results: Overall, 959 participants were included. In this study, 103 had diabetes at baseline (10.7%). Those with lung cancer had the highest frequency of diabetes; 131 people had hyperglycaemia (defined as at least one glucose ≥11.1 mmol/L) in the year after starting an ICPI. The incidence was 55% in those with diabetes at baseline, and 8.6% in those without baseline diabetes. Among 74 with new‐onset hyperglycaemia (without pre‐existing diabetes) 76% was attributable to steroid induced diabetes, with 9.5% due to ICPI Induced diabetes resembling type 1 diabetes. Conclusions: Hyperglycaemia is common in persons receiving an ICPI for cancer, including 8.6% of those without known diabetes. While much of this is due to glucocorticoid use, care is needed to avoid missing those with ICPI‐induced diabetes who are at risk of diabetic ketoacidosis, which is a medical emergency.